E-RUPI – A Future of India’s Digital Payment - Shah, Dr. Rahul; Hariharan, Dr. Vasumathy; Dukhande, Dr. Priyanka (The journal of contemporary issues in business and government, 2022)
e-RUPI is a cashless and contactless instrument that will be used for making digital payments. The digital platform of the payment has been developed by the NPCI i.e., the national payments corporation of India on its platform based on UPI basis. It is digital payment voucher which promises to cut through the need for a payment app, internet banking or even a debit card. The whole digital platform has been devised in consultation & collaboration of Department of Financial services, the Ministry of health and family welfare and the national health authority. The present learning has examined Behaviour and attitude of individuals towards the satisfaction the new digital platform provides thereby creating value addition to the users. It has been evaluated that the recipient of e-RUPI digital payment tool has expressed their optimism towards this platform and claimed that will create a win-win situation for both the users and also the companies. The learning depicts socio-demographic factors, attitude & value creation as a crucial factor towards the adaptation of the e-RUPI.